Dispersion of graphene in ethanol by sonication. (2021) - Cayambe, M.; Zambrano, C.; Tene, T.; Guevara, M.; Tubon Usca, G.; Brito, H.; Molina, R.; Coello-Fiallos, D.; Caputi, L.S.; Vacacela Gomez, C.
Abstract: Graphene is prepared from natural graphite flakes by solvent dispersion and short-sonication time. In this study, we exfoliate few-layer graphene (FLG) directly in ethanol without adding high boiling point solvents, surfactants or polymers. Diverse characterization methods are employed to scrutinize the morphology and quality of the obtained graphene. UV–visible spectrum is characterized by a prominent peak at 269 nm, corresponding to the π to π ∗ transitions of graphene. Raman spectroscopy show that exfoliated FLG to be free of basal-plane defects. Scanning electron microscopy (SEM) evidence semitransparent FLG layers. Transmission electron microscopy (TEM) presents folded (or folded edge) graphene sheets. As the sonication time is reduced, the proposed method shows a great promise for the industrial-scale synthesis of graphene for many applications, from high-frequency electronics to smart coatings.